Humanistisk ledelsesforskning - Keller, Hanne Dauer (Academic Quarter | Akademisk kvarter, 2013)
This issue of Academic Quarter collects articles about humanistic leadership research. Organisation and leadership are traditional themes, which are treated thoroughly within social sciences and commercial disciplines, but these themes have attracted a rising degree of interest from the humanities in recent years.